Proteomic analysis of stored core oil palm trunk (COPT) sap identifying proteins related to stress, disease resistance and differential gene/protein expression - Marhaini Mostapha; Noorhasmiera Abu Jahar; Kamalrul Azlan Azizan; Sarani Zakaria; Wan Mohd Aizat; Sharifah Nabihah Syed Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2018)
Oil palm is the major crop grown and cultivated in various Asian countries such as Malaysia, Indonesia and Thailand. The core of oil palm trunk (COPT) consists of high sugar content, hence suitable for synthesis of fine chemicals and biofuels. Increase of sugar content was reported previously during prolonged COPT storage. However, until now, there has been no report on protein profiles during storage. Therefore, in this study, protein expression of the COPT during the storage period of one to six weeks was investigated using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) coupled with optical density quantification and multivariate analyses for measuring differentially expressed proteins. Accordingly, protein bands were subjected to tryptic digestion followed by tandem mass spectrometry (nanoLC-MS/MS) protein identification. The results from SDS-PAGE showed consistent protein bands appearing across the biological replicates ranging from 10.455 to 202.92 kDa molecular weight (MW) regions. The findings from the principal component analysis (PCA) plot illustrated the separation pattern of the proteins at weeks 4 and 5 of storage, which was influenced mainly by the molecular weights of 14.283, 25.543, 29.757, 30.549, 31.511, 34.585 and 84.395 kDa, respectively. The majority of these proteins are identified as those involved in stress- and defense-related, disease resistance, as well as gene/protein expression processes. Indeed, these proteins were mostly upregulated during the later storage period suggesting that long-term storage may influence the molecular regulation of COPT sap.